Good times, bad times: Taxation and electoral accountability. (February 2017) - Foucault, Martial; Seki, Katsunori; Whitten, Guy D.
Abstract: In this article we address two important and related questions. First, do economic hard times make defeat inevitable for any incumbent? And, second, do voters sanction incumbents for a poor economy whatever the economic policy pursued? To answer these questions, we propose a new theory about the ways in which taxation policies, clarity of responsibility, government ideology, and economic conditions come together to shape election outcomes. We address these questions with a new set of data collected on elections, government policies, and economic measures before and during the current economic crisis. Our findings indicate that taxation policies have effects on incumbent electoral patterns net of economic performance measures, but that these effects differ in theoretically-expected fashions depending on clarity of responsibility, government ideology, and whether or not there has been a recession in the year before an election is held.